O mercado de câmbio brasileiro pela ótica da microestrutura - Collussi, Pedro Barguil (2009)
We address whether spot exchange rate relationship with order flow is derived from flow’s ability to aggregate information regarding future fundamentals that are dispersed in the economy. We test this link using a dataset covering all transaction flows from the Brazilian FX retail market from January 1999 to May 2008 between dealers and two types of counterparties: commercial and financial customers. We show that order flow was reasonably able to explain changes in inflation expectation, a relation that did not remain robust for the selection of others fundamentals, such as GDP and Industrial Production.